Current Collectors for Supercapacitors: Objectives, Modification Methods and Challenges - Miao Liu; Ji‐Chi Liu; Yue Zhang; Xu Han; Hui Li; Zi‐Hang Huang; Tianyi Ma (ChemElectroChem)
Abstract Supercapacitors (SCs) have emerged as promising candidates for efficient and sustainable energy storage devices due to their unique merits, including high power density and long lifespan. However, despite these advantages, SCs face significant challenges related to their relatively low energy density. Current collectors are critical components of SCs, which significantly impacts the efficiency and overall performance by connecting active materials and external devices. However, the reviews on SCs are predominantly focused on electrode active materials or electrolyte materials, with insufficient comprehensive summaries regarding current collectors. This review focuses on the research progress related to current collectors in SCs. Firstly, the article outlines the modification objectives mechanism and inherent nature of SC current collectors. Building on this foundation, the authors further classify the current collector materials towards metallic, carbon‐based, polymers and other ones and highlights their modification strategies. Finally, the future development trends and challenges of SCs current collectors are comprehensively discussed.